Variation in perceived health across gender, working status, educational level, and regional health care expenditure in Spain (2014-2017). - Amanda Godoy-Bermúdez; Araceli Rojo-Gallego-Burin; Luisa Delgado-Márquez; José J Martín-Martín; M Teresa Sánchez-Martínez; M Puerto López Del Amo-González (PLoS ONE, 2023)
A gender perspective was used to analyze whether and how education, unemployment, and per capita public health expenditure were associated with perceived health among the Spanish population between the years 2014 and 2017. Using multilevel methodologies (looking at year, individual, and region) and linear and logistic specifications, we analyzed longitudinal microdata files from the Survey on Living Conditions. The results suggest that women with lower educational levels tend to report worse health than their more educated counterparts. On the other hand, women's bad health was not associated with unemployment, unlike men's. Regional per capita public health expenditure was not associated with perceived health in either men or women.